The neutrophil-to-C3 ratio: unveiling diagnostic efficacy for lupus nephritis and association with reduced retinal vascular density in systemic lupus erythematosus - Maitiyaer, Maierhaba; Li, Peiyi; Li, Huangdong; Jiang, Dingwen; Zhang, Jingyu; Yang, Chuwei; Yang, Xiaobin; Chen, Chengmei; Huang, Wenhui; Liu, Zhiping; Yu, Shuilian (Frontiers in Pharmacology, 2025)
BackgroundLupus nephritis (LN) frequently manifests as a significant complication in systemic lupus erythematosus (SLE) patients, with emerging research indicating a plausible correlation between subclinical retinal involvement and renal manifestations. This study aims to investigate the relationship between the neutrophil-to-C3 ratio (NC3R) and both LN as well as retinal microvasculature damage among SLE patients.MethodsIn this cross-sectional study, a cohort of 220 participants (78 LN and 142 non-LN) was recruited. We assessed clinical indicators and organ involvement and conducted correlation analyses between NC3R and markers of lupus activity. Additionally, we analyzed the diagnostic performance of NC3R in diagnosing LN and constructed ROC curves. Variables such as clinical and laboratory data were screened by univariate and least absolute shrinkage and selection operator (LASSO) logistic regression modeling. After 10-fold cross-validation, the predictive model was built by multivariate logistic regression. We further examined the influence of NC3R on retinal vasculature density based on its cutoff value and conducted correlation analyses accordingly.ResultsThe LN group exhibited a significant increase in NC3R compared to the group without LN (5.9 vs. 4.5, p = 0.007). NC3R demonstrated positive correlations with 24-h proteinuria (R = 0.329, p < 0.001) and systemic lupus erythematosus disease activity index (SLEDAI) score (R = 0.268, p < 0.001). Multiple regression analysis revealed NC3R as an independent risk factor for LN (OR: 2.03, p = 0.025). NC3R was proven valuable in distinguishing LN patients (AUC: 0.613), with an optimal cutoff value of 6.40 (sensitivity: 48.1%, specificity: 72.0%). Our results indicated that the lower NC3R group (NC3R < 6.40) exhibited reduced vascular density, particularly within the macular region. Furthermore, we observed a positive correlation between NC3R levels and vascular density.ConclusionNC3R demonstrated promising potential as a reliable indicator for predicting both LN and retinal microvasculature involvement. Consequently, the pre-treatment evaluation of NC3R had the potential to assist clinicians in identifying potential organ involvement among SLE patients.